Goods Layout Modeling and Simulation Using Genetic Algorithms - Nofri Yudi Arifin (Engineering and Technology International Journal, 2020)
Arrangement of goods in conventional containers takes a long time and relies on the skills of employees or employees. The result of this method is very dependent on the condition of the employee. From the above background, it is necessary to build a computerized system that helps companies to optimize the pattern of arranging goods in containers whose solutions can be searched by genetic algorithms. Genetic algorithm as a search solution method based on natural selection to get an individual with the best gene arrangement, is able to provide a solution on how the pattern of goods arrangement is optimized through an iterative process for several generations with operators namely reproduction, crossing over, and mutation. By entering the input in the form of space and item specifications along with the genetic algorithm operator probability, the genetic process will find a pattern of arrangement of items based on the best fitness or value, i.e. the less empty space is left.